Intellectual property law in the field of sports: specifics of manifestations and features of legal regulation - Харитонов, Євген Олегович; Харитонов, Є. О.; Харитонов, Евгений Олегович; Kharytonov, Yevhen O.; Kharytonov, Evgen; Харитонова, Олена Іванівна; Харитонова, О. І.; Харитонова, Елена Ивановна; Kharytonova, Оlena I.; Ткалич, Максим Олегович; Ткалич, М. О.; Tkalych, Maxym О.; et al. (Universidad del Zulia, 2021)
The article aims to explore the relationships that arise with respect to intellectual property rights in sports. The objectives of the article are to establish points of contact between intellectual property law and sports, as well as a detailed analysis of relevant public relations in terms of intellectual property law and sports law. To achieve the objectives of the article, the authors used a number of scientific methods, among which the main methods are analysis, synthesis and comparative-legal method. The authors of the study concluded that modern sport is developing in close intertwining with intellectual property rights, because only in this way can a sports spectacle be conveyed to a wide range of spectators and consumers in a broad sense. In addition, the range of points of contact between intellectual property and sports law is constantly growing and such can now be called not only patents and trademarks in sports, but also copyright, “image” rights, know-how in sports and the like.

Стаття має на меті дослідити відносини, які виникають щодо прав інтелектуальної власності у спорті. Завданням статті є встановлення точок дотику права інтелектуальної власності та спорту, а також детальний аналіз відповідних суспільних відносин з точки зору права інтелектуальної власності та спортивного права. Для досягнення цілей статті автори використали ряд наукових методів, серед яких основними є аналіз, синтез та порівняльно-правовий метод. Автори дослідження дійшли висновку, що сучасний спорт розвивається в тісному переплетенні з правами інтелектуальної власності, оскільки лише так можна донести спортивне видовище до широкого кола глядачів і споживачів у широкому сенсі. Крім того, коло точок дотику інтелектуальної власності та спортивного права постійно зростає, і такими тепер можна назвати не лише патенти та торгові марки в спорті, а й авторське право, «іміджеві» права, ноу-хау в спорті тощо.
Kharytonov E. Intellectual property law in the field of sports: specifics of manifestations and features of legal regulation / E. Kharytonov, O. Kharytonova, M. Tkalych, I. Bolokan, H. Samilo, Y. Tolmachevska // Сuestiones Рoliticas. - Vol. 39. - Issue 69. - Universidad del Zulia, 2021. – Р. 530-546.
Keywords: WIPO (World Intellectual Property Organization); intellectual property; trademark; design; image rights; ВОІВ (Всесвітня організація інтелектуальної власності); інтелектуальна власність; торгова марка; дизайн; права на зображення; Research Subject Categories::LAW/JURISPRUDENCE